Diversifying food and diets: Using agricultural biodiversity to improve nutrition and health - Fanzo, Jessica; Hunter, Danny; Borelli, Teresa; Mattei, Federico (Routledge, 2013)
One of the world’s greatest challenges is to secure adequate food that is healthy, safe and of high quality for all, and to do so in an environmentally sustainable way. This book explores the role of agricultural biodiversity as a safeguard against hunger, a source of improved dietary diversity and quality, and to strengthen local food systems and environmental sustainability.